CT myocardial perfusion imaging complementing coronary CT angiography in a patient with a history of unstable angina: A case report - Chandra, Christian Rendy; Kasim, Manoefris; Atmadikoesoemah, Celly Anantaria (Indian Journal of Case Reports, 2022)
Coronary computed tomography angiography (CCTA) could show the morphological status of coronary stenosis. Moreover, computed tomography (CT) myocardial perfusion (CTP) could provide additional information to identify hypoattenuating areas that might complement the limitation of CCTA in terms of evaluating the functional status, adding to the diagnostic performance of CCTA. We reported the imaging features of coronary artery disease in a female patient with a history of unstable angina by evaluating the anatomic and functional information through CCTA and CT myocardial perfusion in one stop modality.